Transverse Diameter of Cerebellum: Is There Any Age and Sex Related Change Among Bangladeshi People (KYAMC Journal, 2019)
Background: Cerebellum is ovoid in shape, but is constricted in the median plane, flattened from above downwards and widest from side to side. The cerebellum occupies the posterior cranial fossa, where it is covered by the tentorium cerebelli and lies behind the fourth ventricle, the pons and the medulla oblongata.Objective: The study was done to assess the transverse diameter of cerebellum in relation with age and sex in Bangladeshi people.Materials and Methods: A cross sectional descriptive study was performed on 60 (32 of male and 28 of female) postmortem. The specimens were collected from morgue in the department of Forensic Medicine, Mymensingh Medical College by purposive sampling technique. All the specimens were grouped into four categories: group A (20 to 29 years), group B (30 to 39 years), group C (40 to 49 years), group D (50 to 59 years). Dissection was performed according to standard autopsy techniques. Transverse diameter of cerebellum was measured with the help of slide caliper. For statistical analysis, differences between age groups were analyzed by using unpaired student't' test.Results: The mean (±SD) transverse diameter of cerebellum was 10.53 ± 0.55 cm in group A, 10.09 ± 0.51 cm in group B, 10.03 ± 0.44 cm in group C, 9.72 ± 0.40 cm in group D. The mean differences of the transverse diameter of cerebellum between groups A & C, A & D, A & B, B &D were statistically significant, differences between B & C, D & C were non significant.Conclusion: The study would help to increase the information pool on the transverse diameter of cerebellum of Bangladeshi people.KYAMC Journal Vol. 9, No.-4, January 2019, Page 159-162